Why and how immunohistochemistry should now be used to screen for the BRAFV600E status in metastatic melanoma? The experience of a single institution (LCEP, Nice, France). (16th September 2015) - Long, E.; Ilie, M.; Lassalle, S.; Butori, C.; Poissonnet, G.; Washetine, K.; Mouroux, J.; Lespinet, V.; Lacour, J.P.; Taly, V.; Laurent‐Puig, P.; Bahadoran, P.; et al.
Abstract: Background: Knowledge of the BRAFV600E status is mandatory in metastatic melanoma patients (MMP). Molecular biology is currently the gold standard method for status assessment. Objectives: We assessed and compared the specificity, sensibility, cost‐effectiveness and turnaround time (TAT) of immunohistochemistry (IHC) and molecular biology for detection of the BRAFV600E mutation in 188 MMP. Methods: IHC, with the VE1 antibody, and pyrosequencing analysis were performed with formalin fixed paraffin embedded tumour samples. Results: The BRAFV600E mutation was detected by pyrosequencing in 91/188 (48%) patients. IHC was strongly positive (3+) in all of these 91 cases. IHC was strongly positive in 9/188 (5%) cases in which the molecular testing failed due to non‐amplifiable DNA. Weak or moderate staining was noted in 10/188 (5%) cases in which the molecular biology identified BRAF wild‐type tumours. The ratio of the global cost for IHC/molecular biology testing was 1 : 2.2. The average TAT was 48 h vs. 96 h, for IHC vs. molecular biology testing, respectively. Conclusions: This study showed that VE1 IHC should be a substitute for molecular biology in the initial assessment of the BRAFV600E status in MPP. This methodology needs to be set up in pathology laboratories in accordance with quality control/quality assurance accreditation procedures. Under these strict conditions the question is to know if BRAFV600E‐IHC can serve not only as a prescreening tool, but also as a stand‐alone test (at least in cases displaying an unequivocally staining pattern) as well as an alternative predictive test for samples for which the molecular biology failed.